Kesalahan Penulisan Berita Pada Tugas Siswa Kelas VIIIa SMP Negeri 1 Siak Hulu - Risa Yulfiana; Jamilin Tinambunan (UIR Press, 2022)
This research is motivated by the ability of students to write student news is still relatively low, as this result proves from the value of student assignments made there are only 11 students who reach the KKM, the rest 17 students do not reach the KKM. The purposes of this study are 1) to determine the ability to write news leads on the assignments of class VIII.A SMPN 1 Siak Hulu students, 2) to determine the ability to write news bodies on the assignments of class VIII.A SMPN 1 Siak Hulu students, 3) to determine the writing skills tail (leg) of news on the assignments of class VIII.A students of SMPN 1 Siak Hulu. This research method uses a qualitative approach with the type of research namely library (library research). The source used in this research is the task of the students in writing news on the syllabus of Basic Competencies 3.1 and 4.1 about identifying the elements of news texts and concluding the content of the news for class VIIIA SMP Negeri 1 Siak Hulu. Data collection techniques using hermeneutics. Data analysis techniques collect data, analyze data, present data and provide conclusions. The results of this study indicate that there are several news writing errors on student assignments from the lead, body and news leg, as in the news lead there are 14 student news writing errors from 14 students. In the news body there are 7 data on student errors in news writing, while in the news tail there are 7 data for student news writing errors.